Enumeration of Listeria and Enteric Bacteria of Public Health Significance on Meat Tables Before and After Sales of Meat in Ibadan Municipal Abattoir, Nigeria - Adetunji, Victoria Olusola; Isola, Tajudeen Opeyemi (Pakistan Journal of Nutrition, 2011)
A bacteriological assay was done on meat tables in Ibadan municipal abattoir, Nigeria. Swab samples from 1 cm2 of the surface were obtained from meat tables before and after the sales of meat. The swab samples were analyzed for Listeria sp Count (LSC), Listeria monocytogenes Count (LMC), Coliform Count (CC), Enterobacteriaceae Count (EC) and Salmonella sp Count (SSC). The mean values for LSC, EC and SSC were 8.20±0.06 log10CFU/cm2, 8.81±0.05 log10CFU/cm2 and 7.32±0.20 log10CFU/cm2 respectively for before sales while after meat sales was 10.47±0.05 log10CFU/cm2 (LSC), 11.47±0.03 log10CFU/cm2 (EC) and 11.37±0.04 log10CFU/cm2 (SSC). The mean values for before and after meat sales of Coliform Count (CC) were 8.35±0.07 log10CFU/cm2 and 10.86±0.05 log10CFU/cm2 respectively while Listeria monocytogenes Count (LMC) for before and after meat sales were 7.59±0.06 log10CFU/cm2 and 9.78±0.07 log10CFU/cm2 respectively. The mean values (log10CFU/cm2) showed that EC> LSC>SSC for before meat sales while after sales showed that EC>SSC>LSC. A significat difference (p